New concept for cryptographic construction design based on noniterative behavior - Abdallah Abouchouar; Fouzia Omary; Khadija Achkoun (IAES International Journal of Artificial Intelligence (IJ-AI), 2020)
Nowadays, cryptography especially hash functions require to move from classical paradigms to an original concept able to handle security issues and new hardware architecture challenges as in distributed systems. In fact, most of current hash functions apply the same design pattern that was proved vulnerable against security threats; hence the impact of a potential weakness can be costly. Thus, the solution begins with a deep analysis of divers attack strategies; this way can lead to finding a new approach that enables new innovative and reliable candidates as alternative hash functions. So to achieve this goal, in this article we introduce a new construction design that consists of a non-iterative behavior by combining a parallel block processing and a sequential xor addition process, in order to provide a secure design without changing the expected goal of a hash function, at the same time avoid the use of vulnerable structures.